PENGARUH TEORI FRAUD PENTAGON TERHADAP KECURANGAN LAPORAN KEUANGAN - Auliah Wililyadi, Siti Salwa (COMPETITIVE, 2023)
ABSTRACT            This research aims to determine the influence of elements of fraud pentagon in cheating financial statements on banks listed on the Indonesia Stock Exchange. Sampling techniques in this study using purposive sampling techniques with the final sample there are 20 companies. Data analysis used is logistics regression analysis using IBM SPSS 25 applications. The results showed that: ineffective monitoring as a proxy of opportunity affects the cheating of financial statements, while financial targets as proxies of pressure, change in auditors as proxies of rationalization, change in director as a proxy of competence and frequent number of CEO's picture as a proxy of arrogance has no effect on financial report fraud. Keywords: Fraud, Financial Report Fraud, Pentagon Fraud